Learn from the Japanese Education System - Rifmasari, Yessi; Gusteti, Meria Ultra; Hendriani, Maifit; Rusdinal, Rusdinal; Gistituati, Nurhizrah; Ananda, Azwar (Postgraduate School, Universitas Negeri Padang, 2023)
The reason is that Japan is one of the developed countries that has the best education system in the world and is a mecca or reference for other countries, including Indonesia. One indicator that can be used to see the quality of a country's education is the results of the assessment (PISA) carried out by the Organization for Economic Cooperation and Development (OECD). What is very interesting about Japan's progress, including its educational progress, is that this progress is still framed by the country's noble values. Japanese people are very proud and uphold their traditions and culture. Education is valued and well managed and is based on moral and character development as an integral part of education. The Japanese education system is generally built from a combination of Western ideas and Japanese methods. Even Japan can minimize the unemployment rate, which always increases in every country. The creativity of Japanese education graduates is recognized internationally as an example of success in the automotive sector, namely Honda, and Suzuki, which are always able to innovate their products in a short period. Apart from producing civil servant workers, it is also able to produce experts who can continue to develop the latest research.